Integrasi strategi dan inovasi di sektor perbankan untuk mendukung pertumbuhan dunia usaha di era globalisasi - Fardiana, Sheril (Maliki Interdisciplinary Journal, 2024)
Integration of strategy and innovation in the banking sector is a crucial factor in supporting the growth of the business world in the era of globalization. In facing the challenges of increasingly fierce competition and rapid technological developments, banks also need to adopt innovative approaches that are in line with their business strategies. This research analyzes how the banking sector can integrate strategy and innovation to create added value for customers and increase operational efficiency. The main focus of this study is to identify best practices in combining product and service innovation with effective marketing strategies. In addition, this research also explores the role of digital technology, such as the use of big data and fintech, in strengthening relationships between banks and customers. The research results show that banks that successfully integrate strategy and innovation are able to accelerate growth, increase competitiveness, and provide services that are more responsive to market needs. Thus, the implementation of this integration not only has a positive impact on bank performance, but also contributes to broader economic growth in the era of globalization. This research is also expected to provide insight for practitioners and academics in formulating effective strategies for the banking sector in the future.